Geochemical characteristics and sources of the crude oil of Yan'an formation Yan 9 in Zhao'an area, Ordos Basin, China. (1st February 2020) - He, Yonghong; Fu, Xiaoyan; Li, Tingyan; Wang, Xiujuan; Chang, Yibo; Tang, Longxiang; Liu, Yang
Abstract: A certain scale of Yan 9 reservoir was found in Zhao'an area, but the oil source is not clear. The geochemical characteristics of Yan 9 crude oil and potential source rocks were analyzed by using gas chromatograph-mass method. Analysis results showed that the parent materials of Yan 9 crude oil were sourced from lower aquatic organism and higher terrigenous plants and formed in freshwater- brackish water lacustrine facies. Oil-source correlation results showed that Yan 9 crude oil was derived from the source rocks of Chang 7.